PENDIDIKAN MULTIKULTURAL: KONSEP, TUJUAN, DAN PENERAPANNYA DALAM PEMBELAJARAN - Lailatul Munawaroh, Vicky; Rachmawati, Jeni; Mubin, Nurul (Cahaya Ilmu Bangsa Institute, 2024)
Multicultural education is an approach that emphasizes the importance of recognition, appreciation, and understanding of cultural diversity in the learning process. The main goal of multicultural education is to form individuals who have high social awareness, tolerance, and the ability to coexist in diversity. This research uses a qualitative approach method with a descriptive qualitative literature study research type, which aims to describe and analyze various concepts, objectives, and application of multicultural education in learning. Data collection techniques used by collecting and analyzing books, journal articles, research reports, and other documents that discuss the topic of multicultural education. For this reason, multicultural education is more than just introducing cultural diversity to students, but also aims to instill an understanding of the importance of mutual respect and coexistence with a high sense of tolerance.